2017
DOI: 10.5897/ajmr2017.8487
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infections in intensive care and medical rehabilitation units, and evaluation of antibiotics prescription

Abstract: Although, nosocomial infections (NIs) are considered to be an important cause of mortality and prolonged stay in hospitals, there are only a few studies that are concerned with their prevention and reduction in rehabilitation units. This could be because most NI surveys have been carried out mainly in acute and long-stay in hospitals. As a result, limited information is available on prevention and reduction of NIs in rehabilitation units. The present study is a systematic review that draws attention to the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…These infections can be prevented to a large extent by instituting careful surveillance of bacterial infections, improving hand hygiene, limiting antibiotics overuse and unnecessary invasive procedures. 9 Defining a priori risk factors for HAI can help identify high-risk patients for HAI who need stricter preventive measures and active surveillance of symptoms development. We identified that indwelling urinary catheter, prior surgery and prolonged length of stay were all associated with an increased risk for HAI during the hospitalization at the RW.…”
Section: Discussionmentioning
confidence: 99%
“…These infections can be prevented to a large extent by instituting careful surveillance of bacterial infections, improving hand hygiene, limiting antibiotics overuse and unnecessary invasive procedures. 9 Defining a priori risk factors for HAI can help identify high-risk patients for HAI who need stricter preventive measures and active surveillance of symptoms development. We identified that indwelling urinary catheter, prior surgery and prolonged length of stay were all associated with an increased risk for HAI during the hospitalization at the RW.…”
Section: Discussionmentioning
confidence: 99%
“…Airborne microorganisms are also one of the important factors that cause nosocomial infections in hospitals. Nosocomial infection is considered to be the main obstacle to hospitalization and complications in adults and children, and about 10% of patients will be affected by nosocomial infection [ 11 ]. Nosocomial pathogenic fungi such as Candida and Aspergillus fumigatus can cause pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial pathogenic fungi such as Candida and Aspergillus fumigatus can cause pneumonia. Pneumonia infection is uncommon in immunocompetent patients but can cause death in organ transplant recipients or immunocompromised patients [ 11 , 12 ]. Other pathogens in hospitals such as Escherichia coli , Staphylococcus aureus , respiratory syncytial virus, influenza virus, SARS-CoV-2, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial infections (NI) tend to appear in patients hospitalized in public hospitals, and are not the reason the patient was admitted in the first place [1]. NI may appear during the patients stay in the hospital, or even after the patient have been released from the hospital [2].…”
Section: Introductionmentioning
confidence: 99%
“…NI may appear during the patients stay in the hospital, or even after the patient have been released from the hospital [2]. Other classifications that define NI are: infections occurring 48 h after the beginning of hospitalization, 3 days after patients release or 1 month after surgery [1].…”
Section: Introductionmentioning
confidence: 99%